2010
DOI: 10.1016/j.bpj.2010.10.028
|View full text |Cite|
|
Sign up to set email alerts
|

Hop2-Mnd1 Condenses DNA to Stimulate the Synapsis Phase of DNA Strand Exchange

Abstract: Hop2-Mnd1 is a meiotic recombination mediator that stimulates DNA strand invasion by both Dmc1 and Rad51. To understand the biochemical mechanism of this stimulation, we directly visualized the heterodimer acting on single molecules of duplex DNA using optical tweezers and video fluorescence microscopy. The results show that the Hop2-Mnd1 heterodimer efficiently condenses double-stranded DNA via formation of a bright spot or DNA condensate. The condensation of DNA is Hop2-Mnd1 concentration-dependent, reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Moreover, Hop2-Mnd1 or Dmc1 mutant yeast and mice display epistasis with respect to meiotic chromosome inter-homolog synapsis. Hop2-Mnd1 binds double stranded DNA and induces rapid condensation of large stretches of DNA in vitro, consistent with its requirement for homolog synapsis (Pezza et al, 2010). …”
Section: Resultsmentioning
confidence: 54%
“…Moreover, Hop2-Mnd1 or Dmc1 mutant yeast and mice display epistasis with respect to meiotic chromosome inter-homolog synapsis. Hop2-Mnd1 binds double stranded DNA and induces rapid condensation of large stretches of DNA in vitro, consistent with its requirement for homolog synapsis (Pezza et al, 2010). …”
Section: Resultsmentioning
confidence: 54%
“…A similar activity of Hop2-Mnd1 has been seen with ssDNA-Rad51 filaments (Chi et al 2007). In addition, Hop2-Mnd1 has been shown to dramatically alter the structure of duplex DNA via single molecule analysis, which revealed that Hop2-Mnd1 can promote extensive condensation of duplex DNA (Pezza et al 2010). These findings led to the hypothesis that Hop2-Mnd1 stimulates Dmc1-mediated homology searching by promoting nonspecific binding of duplex by ssDNA-Dmc1 filaments followed by condensation of dsDNA in a manner that increases the rate of homology search (Fig.…”
Section: Hop2 -Mnd1mentioning
confidence: 97%
“…These findings led to the hypothesis that Hop2-Mnd1 stimulates Dmc1-mediated homology searching by promoting nonspecific binding of duplex by ssDNA-Dmc1 filaments followed by condensation of dsDNA in a manner that increases the rate of homology search (Fig. 6E) (Pezza et al 2010).…”
Section: Hop2 -Mnd1mentioning
confidence: 99%
“…Furthermore, in yeast, Dmc1 directs meiotic repair to the homologous chromosome only in the presence of Mnd1 and Hop2 (Zierhut et al, 2004). Recent results demonstrate that the Hop2/Mnd1 protein complex can efficiently condensate double-stranded DNA (dsDNA) to support strand invasion as a key step in stimulating association of the ssDNA-nucleoprotein filament with the dsDNA (Pezza et al, 2010). Mammalian HOP2/MND1 complexes can interact with DMC1 but also with RAD51 in vitro, stimulating the strand exchange activities of both proteins, 35-fold or 10-fold, respectively, but do not show strand exchange activity alone (Petukhova et al, 2005;Enomoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%